The effect of different living arrangement on children´s mental health - Tinna María Ólafsdóttir 1992- (2019)
The purpose of this study was to examine the impact different living arrangements have on mental health among Icelandic adolescents and whether parent’s education and financial situation had buffering effect. Mental health was measured by examining: depression symptoms, anxiety symptoms and level of anger. The different living arrangements were: an intact family, equal physical custody, living mostly with mother and living mostly with father. This study used a random sample of 4.045 elementary school students that participated in a national survey called, Youth in Iceland 2018, originally conducted by ISCRA. The results revealed that there was a significant difference in mental health between different living arrangements groups. Children in intact families measured lower in depression, anxiety and anger than children in other family forms. Moreover, children in equal physical custody measured slightly lower than children in sole physical custody in anger and depression but after controlling for parents education and financial situation there was no significant difference between those living in equal physical custody and with single parent. Keywords: Psychology, custody, living arrangement, mental health, equal physical custody Markmið þessarar rannsóknar var að skoða hvort munur væri á andlegri líðan unglinga á Íslandi eftir búsetufyrirkomulagi hjá foreldrum. Líðan var metin með því að skoða: þunglyndiseinkenni, kvíðeinkenni og reiði. Eftirfarandi búsetufyrirkomulag var borið saman: kjarnafjölskylda, jöfn búseta, býr aðallega hjá móður, býr aðallega hjá föður. Notað var handahófskennt úrtak úr gögnum frá Rannsóknum og greiningu sem söfnuðu gögnum undir yfirskriftinni Ungt fólk 2018. Niðurstöður leiddu í ljós að marktækur munur var á andlegri líðan, eftir búsetufyrirkomulagi. Þeir sem bjuggu með báðum foreldrum mældust með betri andlega heilsu en börn sem bjuggu við annað fyrirkomulag. Þá mældust börn sem bjuggu jafnt hjá báðum foreldrum sínum með færri þunglyndis einkenni og reiði en þau sem bjuggu einungis ...